(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
The studio is located in the area of the National Systems of Innovation (SNI), where innovation is seen as a social and interactive process that links to various actors, which is why we speak of a specific social environment and systemic in it the creation of knowledge is not only a result of internal development of firms (formal, informal, codified and tacit), but the product of recombination of codified knowledge and tacit knowledge socialization from this relationship, as forms framed develops networks where all social relations, rules and political constraints that shape the innovation environment. The objective was to approximate the actual operating form and the way they link the various Public and Private Institutions (PPI) that make up the Regional Innovation System (NIS) in Aguascalientes, from the perspective of inter-networking. Purposive sampling was adopted to this end we used a methodological strategy based on nonparametric statistical treatment. The results obtained for the IPP reiterate the trend that some are not as agile IPP to build relationships around the innovation, this means that public space is not yet generating positive externalities that are required to promote the endogenous development of the region, the absence of intermediate structures is manifested in communication gaps and decision addressing the problems facing these institutions and in general to SRI.